2023
DOI: 10.3390/ijms241813700
|View full text |Cite
|
Sign up to set email alerts
|

A Genome-Wide Analysis of the Pentatricopeptide Repeat Protein Gene Family in Two Kiwifruit Species with an Emphasis on the Role of RNA Editing in Pathogen Stress

Aidi Zhang,
Yuhong Xiong,
Fang Liu
et al.

Abstract: Kiwifruit is a perennial fruit tree with high nutritional and economic value; however, various pathogen stresses have resulted in reductions in its yield and quality. Pentatricopeptide repeat proteins (PPRs), characterized by tandem repetitions of 35 amino acid motifs, play roles in RNA editing, mRNA stability, and splicing. They may also regulate plant development and growth. Nevertheless, the roles of PPRs in plant development and disease resistance remain unclear. In this study, we focused on the roles of P… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…The Ka/Ks values were calculated to evaluate the selection pressure during evolution [3]. We found that the Ka/Ks values of the duplicate pairs identified above were mostly less than 1, indicating that these genes evolved under purifying selection.…”
Section: Synteny Analysis Of Lrr-rlps In Kiwifruitmentioning
confidence: 97%
See 2 more Smart Citations
“…The Ka/Ks values were calculated to evaluate the selection pressure during evolution [3]. We found that the Ka/Ks values of the duplicate pairs identified above were mostly less than 1, indicating that these genes evolved under purifying selection.…”
Section: Synteny Analysis Of Lrr-rlps In Kiwifruitmentioning
confidence: 97%
“…Kiwifruit (Actinidia Lindl. ), classified in the Actinidiaceae family and the genus Actinidia, is commonly referred to as the "King of Fruits" due to its exceptionally high contents of vitamin C, minerals, dietary fiber, and other beneficial metabolites [1][2][3]. Originating in China, kiwifruit has become a significant cash crop, gaining popularity worldwide for its flavor and nutritional attributes [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation